(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Carboxyl and nitrite functionalized graphene quantum dots (CNGQDs) was used for the efficient synthesis of Î±-oximinoketones under free mineral acid conditions at room temperature. CNGQDs was prepared via o-nitrozation of carboxyl and hydroxyl graphene quantum dots (CHGQDs) and used as a nitrosonium source and also as an efficient acidic catalyst for the synthesis of Î±-oximinoketones. The structure of the catalyst was characterized by FT-IR, XRD, TGA and photoluminescence techniques. The structures of the synthesized products were confirmed by FT-IR, 1H-NMR and 13C-NMR spectroscopic techniques. Stability and recyclability of the prepared homogeneous catalyst was studied in details. Reaction times and yields of the products were compared with previous reported methods resulting high yields and also shorter reaction times.